ANTHROPOMETRIC ASSESSMENT OF PAEDIATRIC FLAT FOOT: A DIAGNOSTIC ACCURACY STUDY - Hameed, Nadira; Baseer, Najma; Huma, Zilli; Javed, Sumaira; Raza, Tauseef; Sadaf, Aisha (Journal of Ayub Medical College Abbottabad, 2020)
Background: Flat-foot involves total collapse of medial longitudinal arch, which becomes distressful when children begin to stand on their feet. Flat foot is usually diagnosed on clinical examination, however due to lack of a standardized protocol, there are conflicting views regarding its management. The objective of this study is to determine the accuracy of radiographic and podometric measurements in diagnosing paediatric flat foot. Methods: It was a cross sectional diagnostic accuracy study. Eighty-four children of preschool and school going age were recruited equally into control and flat foot groups. Each child was examined clinically and was further classified into having flexible or rigid flat foot. For radiographic assessment, lateral and anteroposterior foot radiographs were taken while footprints were captured using podoscope and analysed with FREESTEP software. The diagnostic accuracy and correlation among different parameters were also computed. Results: Clinically, of the 42 children in the flat foot group, 26 had flexible while 16 had rigid flat foot. Of these, 40 children were flat footed on one or more radiographic parameters, while 36 had podometric measurements within the flat foot range. Radiography had the sensitivity and specificity of 95% and 69%, respectively, while podometry was 86% sensitive and 47% specific. Clark's angle had highest sensitivity of 90%, with AUC of 0.952. A strong positive correlation was found between arch index and talocalcaneal angle (r=.805). Conclusion: The diagnostic accuracy of radiography was more than podometry. More specific and sensitive parameters in combination with clinical assessment may prove to be useful in the management of paediatric flat foot. Keywords: Flat foot; Flexible flat foot; Rigid flat foot; Podoscope; Foot arch; Sensitivity; Preschool children; School going children